Extraction of solasodine from dry fruits and leaves of Solanum laciniatum Ait. and the synthesis of 16-dehydropregnenolone acetate from solasodine by phase-transfer catalysis - Jiradej Manosroi (2018)
A simple extraction and isolation process of solasodine, a natural precursor to synthesize steroidal drugs, from fruits and leaves of Solanum laciniatum Ait. was developed. The optimum concentration of 2-propanol for the extraction of crude glycosides was 70%. The suitable hydrolysis condition of solasodine from crude glycosides was by 1 N hydrochloric acid in 2-propanol. Pure solasodine from both fruits and leaves of Solanum laciniatum Ait. was obtained without any requirement of column chromatography. The yield of pure solasodine were 0.34±0.04% and 0.44±0.16% of the dry weight of fruits and leaves, respectively. The maximum yield of 37.0% of pure 16-DPA was obtained by using tetrabutylammonium hydrogen sulfate as a phase-transfer catalyst and potassium dichromate as an oxidizing agent. The results indicated the novel economic with environmental friendly method of solasodine extraction and synthesis of 16-dehydropregnenolone acetate from solasodine by phase-transfer catalysis. © ISHS 2005.